Pengaruh Green Accounting dan Corporate Social Responsibility terhadap Profitabilitas - Ziral Raditya Aziz; Masiyah Kholmi (Jurnal Ekonomi Akuntansi dan Manajemen, 2024)
This study aims to examine the effect of Green Accounting and Corporate Social Responsibility on Profitability. The object of this research is the mining sub-sector energy sector companies listed on the IDX in 2019-2021 with certain criteria. The sampling method in this study was purposive sampling by producing a sample of 45 samples. The data analysis technique in this study used Stata14 with the results of Green Accounting research affecting profitability and Corporate Social Responsibility having no effect on profitability. Keywords: Green Accounting, Corporate Social Responsibility, Profitability